RADIOECOLOGICAL INVESTIGATIONS IN THE SEA OF JAPAN AND THE NORTH-WEST PART OF THE PACIFIC OCEAN AFTER THE ACCIDENT AT THE NPP “FUKUSHIMA-1” IN JAPAN: PRELIMINARY RESULTS - A. I. Nikitin; V. P. Ramzaev; V. M. Osokin; A. S. Sergeev; A. V. Sevastyanov; R. A. Aliev; G. B. Artem’ev; G. Ya. Bruk; P. S. Vaganov; E. N. Vekhov; A. Yu. Vyakhirev; I. N. Titov; et al. (Радиационная гигиена)
In the period from April 22 until May 20, 2011, an expedition aboard the research vessel “Pavel Gordienko” (Russian Federation) was carried out to the Sea of Japan and the Kuril-Kamchatka region of the Pacific Ocean. The main aim of the expedition was to study radioactive contamination of the atmospheric air and sea water after the accident at the NPP “Fukushima-1” in Japan. This paper provides preliminary results on the activity concentration of 137Cs and 134Cs in twenty four samples of sea water. The activity concentrations of 131I, 137Cs, 134Cs, and 7Be for twenty nine samples of atmospheric aerosols, which were sampled during the expedition, are also given. Despite the preliminary character of the results of this study, a generic conclusion on a negligible radiological impact of the anthropogenic gamma-ray-emitting radionuclides for the Far-Eastern sea areas of Russia can be reached. The investigations have been supported by a grant from the Russian Geographical Society.